HUBUNGAN HIPERKALEMIA DENGAN ACTIVITY DAILY LIVING PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA - Cherlyn Eva Taryono (2022)
Chronic kidney failure is permanent kidney damage so that the kidneys cannot carry out their functions properly, namely managing waste in the body, this makes potassium levels in the body increase, increased potassium levels > 5 mmol/L, namely hyperkalemia, becomes a life-threatening problem because it can cause complications. fatal, which leads to cardiac arrest, high potassium levels also cause muscle cramps, muscle fatigue, weakness and loss of muscle movement that interferes with the ability to carry out Activity Daily Living (ADL). The purpose of this study was to identify the relationship between hyperkalemia and activity daily living in chronic renal failure patients undergoing hemodialysis. This study used a quantitative research design with cross sectional method and analyzed using the Spearman Correlation Test. The sampling method used purposive sampling as many as 33 respondents. The instrument used in this study is the Barthel index. The results of this study indicate that there is a negative relationship with a very strong correlation between hyperkalemia and activity daily living with a value (p-value 0.00) and a value (r Spearman = - 0.943).